O "efeito fotoelétrico" na inserção da física moderna no ensino médio - Nascimento, José Paulo (2023)
The present work proposes a sequence of lessons on the Photoelectric Effect for 1st-year high school class, with the aim of significantly improving students's understanding of Physics, using a methodology based on David Ausubel's theory of Meaningful Learning. The photoelectric effect is an important phenomenon in modern physics and is present in various technological applications, such as solar cells and optoelectronic devices. However, many students have difficulty understanding the concepts related to this phenomenon due to its abstract and complex nature. Based on this, our methodological proposal defends the importance of the student's prior knowledge for the construction of new concepts, using everyday examples and simple experiments to facilitate the relationship between what is to be taught and what the student already knows. The material developed was applied in 1styear high school classes at the "Hunney Everest Piovesan" State Elementary and High School and was structured in a sequence of eight lessons, totaling four months of activities. During this period, the contents were presented, activities were applied, and data were collected for subsequent analysis. The expectation is that the proposed methodology will have a positive impact on students' learning and can be used as a reference for future studies on the subject. During the process, activities were proposed that involved group work, problem-solving, and the use of audiovisual resources, as well as practical experiments to illustrate theoretical concepts. At the end, an evaluation was carried out on the content and the application of the didactic material. We hope that the proposed methodology will help improve students' understanding of the photoelectric effect, highlighting the importance of using materials that seek to relate theoretical concepts to concrete situations in everyday life. We also hope that the proposed methodology can contribute to the development of more effective didactic materials in teaching physics, especially in complex topics such as the photoelectric effect. With this, we hope to form more critical students capable of applying physical concepts in everyday situations, contributing to the formation of more aware and prepared citizens for the challenges of the contemporary world.